2024
DOI: 10.1111/medu.15385
|View full text |Cite
|
Sign up to set email alerts
|

Medical education in Syria at a time of crisis: Analysis of the results of the knowledge‐based National Medical Examination

Jameel Soqia,
Jamal Ataya,
Rakan Saadoun
et al.

Abstract: ObjectiveThis study explored how the Syrian crisis, training conditions, and relocation influenced the National Medical Examination (NME) scores of final‐year medical students.MethodsResults of the NME were used to denote the performance of final‐year medical students between 2014 and 2021. The NME is a mandatory standardised test that measures the knowledge and competence of students in various clinical subjects. We categorised the data into two periods: period‐I (2014–2018) and period‐II (2019–2021). Period‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, the authors recommend the addition of two domains: the perception of available resources which should be designed to measure the available hospital resources and investigate how it affects working and learning; secondly, the perception of psychological support which should be designed to evaluate the psychological burden of working in under-resourced and chaotic hospital setting in a war-ravaged country like Syria. Availability of resources affects residents ability to practice medicine effectively and henceforth learning on the job especially in an age where medical technology and equipment are fundamental for everyday practice; although literature of the effect of lack of resources on teaching hospitals in Syria are scarce, recent papers has highlighted the effect of war and resource availability on medical students’ performance [ 37 ] and their perception of the learning environment [ 21 , 38 , 39 ]; some residents can miss out the chance to practice essential procedural skills for this reason [ 34 ]. As for the psychological health domain, studies have numerously showed the negative effect of war on psychological health of residents and having items to address, assess and bring forward this important area in our vulnerable context is very important from an educational perspective as well as wellbeing perspective [ 20 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors recommend the addition of two domains: the perception of available resources which should be designed to measure the available hospital resources and investigate how it affects working and learning; secondly, the perception of psychological support which should be designed to evaluate the psychological burden of working in under-resourced and chaotic hospital setting in a war-ravaged country like Syria. Availability of resources affects residents ability to practice medicine effectively and henceforth learning on the job especially in an age where medical technology and equipment are fundamental for everyday practice; although literature of the effect of lack of resources on teaching hospitals in Syria are scarce, recent papers has highlighted the effect of war and resource availability on medical students’ performance [ 37 ] and their perception of the learning environment [ 21 , 38 , 39 ]; some residents can miss out the chance to practice essential procedural skills for this reason [ 34 ]. As for the psychological health domain, studies have numerously showed the negative effect of war on psychological health of residents and having items to address, assess and bring forward this important area in our vulnerable context is very important from an educational perspective as well as wellbeing perspective [ 20 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%